2600 Phrases for Setting Effective Performance Goals : Ready-to-Use Phrases That Really Get Results. - Falcone, Paul (AMACOM, 2011)
As a manager, you arenÆt truly successful unless your employees are as well. Helping them establish compelling, actionable performance goals is the first and most important step, and 2600 Phrases for Setting Effective Performance Goals is there to lend a hand. A natural follow-up to the bestselling 2600 Phrases for Effective Performance Reviews, this quick-reference guide provides readers with ready-to-use performance goals organized by the characteristics and core competencies used most often in the appraisal process. From attendance and attitude to teamwork and time management, managers will.